STRATEGIES TO DEVELOP COASTAL SOCIETY MICRO INDUSTRIES THROUGH KOPERASI WANITA NELAYAN MINA MELATI DESA BENDAR KECAMATAN JUWANA - Yusak Eko Kristanto; Margaretha Suryaningsih; Ari Subowo (Journal of Public Policy and Management Review, 2012)
Coastal society is a society which life in coastal district with huge potent of fishery resources but ironically this society is still near with image of poverty. For that reason, they need an establish step to empower the coastal society so they can use the fishery resources that they have optimally.Micro Industries development through Fish Processing is one of the solution .Through this effort, exploitation of fishery potent is done with adding economic value using various processing technique. Desa Bendar as a model of coastal district is developed micro industries fish processing where there are The Koperasi Wanita Nelayan that have a big role on it. But so far, the development still can not be done maximal way because of some trouble. An effective strategy is needed to surpass it.The goal of this research is to recommend strategy for developing coastal society micro industry through The Koperasi Wanita Nelayan Mina Melati in Desa Bendar.. The strategy is given by analyzed the condition of micro industries development and analysis of internal and external environment of Koperasi as the actor of development through SWOT analysis. After that step is done, the next step is identification of strategies issues and tested it using Litmus Test to determine strategically existing development issue. In this qualitative research is using Snowball Sampling. The methods of collecting data in this research is in-depth interview and chose the informant used purposive system.From this research is obtained development strategy interconnected with institutional development and Koperasi organization and strategy about optimality the role of koperasi as main facilitator to cooperate with another stakeholder especially the government in develop access capability in adding capital.